Prognoses and long-term outcomes of nasopharyngeal carcinoma in Han and Uyghur patients treated with intensity-modulated radiotherapy in the Xinjiang Autonomous Region of China. - Ruozheng Wang (PLoS ONE, 2014)
OBJECTIVES:The objective of this study was to investigate the long-term outcomes and prognostic factors for nasopharyngeal carcinoma (NPC) in Han and Uyghur patients treated with intensity-modulated radiotherapy (IMRT) in the Xinjiang region of China. MATERIALS AND METHODS:One hundred twenty-one Han and 60 Uyghur patients with newly diagnosed NPC without distant metastasis received IMRT at the Affiliated Tumor Hospital of Xinjiang Medical University between 2005 and 2008. The Kaplan-Meier method was used to estimate survival rates, and the log-rank test was used to evaluate differences in survival. RESULTS:Comparing Han and Uyghur patients, the 5-year overall survival (OS), disease-free survival (DFS), local control (LC), regional control (RC), and distant metastasis-free survival (DMFS) rates were 81.9% vs 77.6% (P = 0.297), 72.1% vs 65.6% (P = 0.493), 88.3% vs 86.5% (P = 0.759), 95.0% vs 94.6% (P = 0.929), and 79.1% vs 75.2% (P = 0.613), respectively. Multivariate Cox proportional hazards regression identified the following independent prognostic factors in Han patients: N stage (P = 0.007) and age (P = 0.028) for OS, and age (P = 0.028) for DFS. OS differed significantly between Han and Uyghur patients >60 years old group (P = 0.036). Among Uyghur patients, the independent prognostic factors were age for OS (P = 0.033), as well as N stage (P = 0.037) and age (P = 0.021) for DFS. Additionally, Uyghur patients were less likely to experience mucositis and dermatitis than Han patients. CONCLUSION:Han and Uyghur patients with NPC had statistically significant differences in age, smoking history, and N staging. There was no significant difference in overall treatment outcomes with IMRT between these 2 ethnic populations in Xinjiang, China.